Scientific Paper Writing Training for Students of the Public Sector Accounting Study Program, Ambon State Polytechnic - Jacomina Vonny Litamahuputty; Maria Juneferstina P (Konsienti : Community Services Journal, 2025)
This community engagement initiative was designed to address the persistent challenge of limited scientific writing proficiency among vocational students, particularly in the Public Sector Accounting Study Program at Ambon State Polytechnic. The program implemented a structured training model grounded in the Participatory Action Research (PAR) approach, encompassing five phases: needs assessment, module development, workshop facilitation, individualized mentoring, and post training evaluation. A total of 21 final year students participated in a series of interactive sessions focusing on IMRAD structure, academic language, referencing techniques, and reflective practice. Quantitative findings revealed a significant improvement in writing scores following the intervention, while qualitative analysis indicated increased academic self efficacy and peer led knowledge exchange. The program not only enhanced technical writing competencies but also catalyzed the emergence of a collaborative academic culture within the vocational setting. This initiative offers a replicable model for embedding scientific writing development into vocational curricula, contributing to institutional goals of research literacy and publication readiness.